Co-Creation in participatory epidemiology. (13th November 2019) - Bach, M; Santos-Hövener, C; Jordan, S
Abstract: Background: Participatory epidemiology aims to involve public health professionals, health activists, and community representatives in epidemiological studies. Paramount are equitable research partnerships for identifying the causes of health problems, generating data, and finding ways to address health related issues. Alongside the research process, co-creation informs various aspects of participatory epidemiology. Methods: A scoping review was conducted to develop the conceptual foundations of participatory epidemiology. Workshops with staff from public health administration and public health practitioners were held to check feasibility of the concept for public health monitoring, policy making and the development of relevant public health recommendations. From this research, principles and practices of co-creation were identified. Results: Co-creation is of importance for participatory epidemiology. 1) Methodologically: Co-creation asks to apply multiple perspectives (research, practice, communities) in data collection and synthesis, what may require the adaption of a given study design. 2) Research practice: Co-creation in participatory epidemiology means producing epidemiologic evidence while contributing to concrete public health interventions, two goals that have to be balanced. 3) Personal attitudes: In participatory epidemiology academic researchers, practitioners, and community representatives are requested to acknowledge each other as co-researching partners, which can be challenging for each of them. Conclusions: Co-creation is a prerequisite for establishing equitable research partnerships. In participatory epidemiology, co-creation offers ways to produce meaningful knowledge for research and practice. Main messages: Participatory epidemiology offers ways of producing epidemiologic evidence while contributing to public health practice. Co-creation is a prerequisite, way, and attitude to conduct meaningful research, hopefully for all of those who are involved.